Performance of Wheat (Triticum aestivum L.) in Response to Different Levels of Irrigation and Nitrogen Application - Perveen, Suriaya; Salam, Md. Abdus; Uddin, Md. Romij; Haque, Md. Ekram ul; Haque, Md. Ekram ul (Journal of the Bangladesh Agricultural University, 2024)
Balanced fertilizer management and optimum irrigation are essential for maximizing yield of wheat and at the same time excess application of water and nitrogen fertilizer are not economically efficient and can create environmental problems. Therefore, an experiment was conducted at the Central Farm, Bangladesh Agricultural University, Mymensingh from November 2018 through March 2019 to determine the optimum level of irrigation and rate of nitrogen required to achieve the maximum yield of wheat. The experiment consisted of four levels of irrigation i.e., no irrigation (I0), one irrigation at Crown Root Initiation (CRI) stage (I1), two irrigations at CRI and 40 Days After Sowing (DAS) (I2) and three irrigations at CRI, 40 and 60 DAS (I3), and four rates of nitrogen i.e., no nitrogen (N0), application of 60 kg N ha-1 (N1), application of 120 kg N ha-1 (N2) and application of 180 kg N ha-1 (N3). The experiment was laid out in a split-plot design with three replications where irrigation level was assigned to the main plots and nitrogen level in subplots. BARI Gom28 was used as the test variety. The maximum grain yield (4.00t ha-1) was found with three irrigations at CRI, 40 and 60 DAS. Application of 180 kg N ha-1 gave the highest grain yield (4.54 t ha-1) which was the cumulative effect of highest number of effective tillers hill-1, longest spike and highest number of grains spike-1 in this treatment. Yield and yield contributing characters like effective tillers hill-1, number of grains spike-1, grain yield and straw yield were significantly influenced by interaction of irrigation and nitrogen. The highest grain yield (5.22t ha-1) was obtained in three irrigations at CRI, 40 and 60 DAS with application of 180 kg N ha-1 which was statistically identical to two irrigations at CRI and 40 DAS with the application 120 kg N ha-1. In the economic analysis of this study, the highest Benefit Cost Ratio (BCR) (2.41) was found from two irrigations at CRI and 40 DAS with application of 120 kg N ha-1 (I2N2). Therefore, the treatment combination of two irrigations at CRI and 40 DAS with application of 120 kg N ha-1 was effective and economic for producing higher grain yield of wheat. J Bangladesh Agril Univ 18(4): 968–974, 2020 https://doi.org/10.5455/JBAU.13958